PEMBUATAN GAME PLATFORMER “NEO THE DEFENDER OF NATIVE LAND” PADA PLATFORM ANDROID - Darwin Darwin; Jeanny Pragantha; Darius Andana Haris (Fakultas Teknologi Informasi Universitas Tarumanagara, 2019)
“Neo The Defender Of Native Land” is a platformer game for Android. Where the player must save the world by killing the boss and save citizens. This game use two-dimensional graphics. The game uses a virtual button control to run, attacking. This game created by Unity game engine with C# as programming language and photoshop to use to make object, animation. Testing was done by the blackbox testing, alpha testing by lecturer, and beta testing by surveying 34 respondens. Test results show that most responden have played platformer games before. the test results show that the